Detection of prostate carcinoma with contrast‐enhanced sonography using intermittent harmonic imaging - Halpern, Ethan J.; Ramey, John R.; Strup, Stephen E.; Frauscher, Ferdinand; McCue, Peter; Gomella, Leonard G. (Cancer, 2005)
BACKGROUND The purpose of this study was to assess prostate carcinoma detection and discrimination of benign from malignant prostate tissue with contrast‐enhanced ultrasonography. METHODS In all, 301 subjects referred for prostate biopsy were evaluated with contrast‐enhanced sonography using continuous harmonic imaging (CHI) and intermittent harmonic imaging (IHI) with interscan delay times of 0.2, 0.5, 1.0, 2.0 seconds, as well as continuous color and power Doppler. Targeted biopsy cores were obtained from sites of greatest enhancement, followed by spatially distributed cores in a modified sextant distribution. RESULTS Carcinoma was detected in 363 biopsy cores from 104 of 301 subjects (35%). Carcinoma was found in 15.5% (175 of 1133) of targeted cores and 10.4% (188 of 1806) of sextant cores (P < 0.01). Among subjects with carcinoma, targeted cores were twice as likely to be positive (odds ratio [OR] = 2.0, P < 0.001). Clustered receiver operating characteristic (ROC) analysis of imaging findings at sextant biopsy sites yielded the following Az values: precontrast gray scale: 0.58; precontrast color Doppler: 0.53; precontrast power Doppler: 0.58; CHI: 0.62; IHI (0.2 sec): 0.64; IHI (0.5 sec): 0.63; IHI (1.0 sec): 0.65; IHI (2.0 sec): 0.61; contrast‐enhanced color Doppler: 0.60; contrast‐enhanced power Doppler: 0.62. A statistically significant benefit was found for IHI over baseline imaging (P < 0.05). CONCLUSIONS The carcinoma detection rate of contrast‐enhanced targeted cores is significantly higher when compared with sextant cores. Contrast‐enhanced transrectal sonography with IHI provides a statistically significant improvement in discrimination between benign and malignant biopsy sites. However, given the relatively low ROC areas, this technique may not be sufficient to predict which patients have benign versus malignant disease. Cancer 2005. © 2005 American Cancer Society. The purpose of this study was to assess prostate carcinoma detection and discrimination of benign from malignant prostate tissue with contrast‐enhanced ultrasonography.